1986
DOI: 10.1002/pros.2990080408
|View full text |Cite
|
Sign up to set email alerts
|

Association states of androgen receptors in nuclei of human benign hypertrophic prostate

Abstract: Androgen receptors (AR) were quantified in nuclei purified from unfractionated benign hypertrophic prostate (bph) tissue and from separated epithelium and stroma from bph specimens. Both epithelial and stromal cell nuclei contained AR, although concentrations in epithelial cell nuclei were higher and more variable. Variations in AR levels in epithelial cell nuclei reflected variations in unfractionated-tissue nuclei. Nuclear AR were further characterized regarding extractability with or resistance to 0.6 mol/l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

1987
1987
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 50 publications
1
15
0
1
Order By: Relevance
“…Androgens play a role in the development and maintenance of BPH particularly in the prostatic epithelium, which is supported by androgen receptor expression in prostatic epithelium (34,35), reduction in hyperplastic prostate mass, primarily of the epithelium, with androgen deprivation (36), and the absence of BPH in men who are castrated before puberty (37) or who are deficient in 5a-reductase-2 (38,39). Early work on risk factors for BPH suggested that men with alcoholic cirrhosis of the liver, which leads to decreased testosterone concentrations and in some cases increased estrogen concentrations (9), were less likely to have BPH nodules at autopsy, although study methods did not always take into account differing age distributions among cases and controls and findings were not entirely consistent between studies (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Androgens play a role in the development and maintenance of BPH particularly in the prostatic epithelium, which is supported by androgen receptor expression in prostatic epithelium (34,35), reduction in hyperplastic prostate mass, primarily of the epithelium, with androgen deprivation (36), and the absence of BPH in men who are castrated before puberty (37) or who are deficient in 5a-reductase-2 (38,39). Early work on risk factors for BPH suggested that men with alcoholic cirrhosis of the liver, which leads to decreased testosterone concentrations and in some cases increased estrogen concentrations (9), were less likely to have BPH nodules at autopsy, although study methods did not always take into account differing age distributions among cases and controls and findings were not entirely consistent between studies (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…24 Obesity has effects on many hormones, including an increase of estrogen and decrease of testosterone levels, 1 due to aromatization of androgens to estrogens in the adipose tissue. 25 Androgens are involved in the development and maintenance of BPH, as supported by androgen receptor expression in prostate epithelium, 26,27 and by the observation of high testosterone levels in men with prostate cancer in several, although not all studies. 28 Androgen receptor gene polymorphisms (and particularly a CAG repeat length of o21 and a CGN repeat length o16) was also associated with the risk of BPH in a study from Olmsted County, MN, USA.…”
Section: Discussionmentioning
confidence: 99%
“…Smaller fragments damaged by TUR were discarded and only those from which charred material could be removed to leave satisfacto rily uninjured samples were used [15]. Homogenization of tissue, preparation of nuclei and exhaustive nucleolysis to yield total pop ulations of nuclease-extractable and nuclease-resistant androgen re ceptors have been described [13,14], Under the conditions em ployed, 'nuclease-resistant' described those receptors which had not been solubilized during a digestion procedure following which no more nuclear material could be released by the action of micrococ cal nuclease (used routinely) or any other nuclease alone. In this report, 'nuclease-extractable' describes those androgen receptors which have been solubilized during such a procedure.…”
Section: Methodsmentioning
confidence: 99%
“…However, this new emphasis presents fresh complications. Determina tions on high-ionic-strength extracts of nuclei [1][2][3][4][5] ig nore a considerable population of androgen receptors which is resistant to such treatment [2][3][4]8], and which has, by virtue of its association with the nuclear matrix, been proposed as a biologically active component [2], In both cancer and benign prostate hypertrophy (BPH), nuclear androgen receptors may differ quantitatively or in intranuclear deployment from the normal condition [8,[10][11][12], Moreover, the intranuclear deployment of androgen receptors can differ markedly between cancer and BPH samples of similar quantitative receptor con tent [13,14], Anomalies in androgen receptor distribu tion may relate not only to the aetiology of the diseases but also to the disparate development of carcinoma and BPH. This report describes in greater detail the dissimi larities in intranuclear deployment of androgen recep tors in prostate cancer and BPH, and also recounts pre liminary investigations into the relationships of andro gen receptors and the expression of genes which may be implicated in the initiation or progression of cancer.…”
Section: Introductionmentioning
confidence: 99%